The central limit theorem for the sums of renewal processes - Kaminskienė, B. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Б. Каминскене. Центральная предельная теорема для сумм процессов восстановленияB. Kaminskienė. Centrinė ribinė teorema atstatymo procesų sumoms